Impact of Accounts Receivable Write-Off Policy on Stock Fluctuations of State-Owned Bank Companies - Rahmawati; Hishaly GH, Nur; Damirah, Damirah; Wahyuni Nur, Sri; Maricar, Rezvanny; Arismunandar, Andi Patotori (Program Studi Perbankan Syariah, IAIN Palopo, 2025)
This study aims to examine the impact of the announcement of debt write-off policy on the abnormal returns of state-owned banking stocks. A quantitative method with an event study approach is employed to analyze market reactions to the announcement. The research sample consists of four state-owned banks listed on the Indonesia Stock Exchange, with stock price data collected from December 29, 2023, to November 19, 2024. The findings indicate a negative impact of the debt write-off policy announcement on the cumulative average abnormal return (CAAR), suggesting that investors perceive the policy as unfavorable. This reaction is associated with potential moral hazard in its implementation. The study underscores the importance of transparency and government assurances regarding financial performance in the context of such policies. It also recommends that financial practitioners consider the implications of policy announcements on stock market reactions. This research contributes to the understanding of market efficiency theory in responding to new information and provides insights for policymakers and investors. Future studies are encouraged to explore long-term impacts and incorporate qualitative approaches or additional variables, such as global economic events, to offer a more comprehensive analysis.